Measurement of temperature on the bearing surface of an industrial die and assessment of the heat transfer coefficient in hot extrusion of aluminium: a case study. (20th December 2005) - Tercelj, M.; Kugler, G.; Turk, R.; Cvahte, P.; , P. Fajfar
Under the conditions of industrial hot extrusion of aluminium we used an improved method of temperature measurement on the bearing surface of the die and assessed the heat transfer coefficient from the extruded profile on the die bearing surface. The measurements were carried out by means of a split die on the interface of which channels were made for the embedding and welding of thermocouples close to the die-bearing surface. Measurements were carried out for the case of nitrogen cooling of the die and for the case of non-cooling. The extrusion speed was increased up to the melting point of Mg2 Si (eutectic phase) with a known melting temperature on the extruding profile surface. Such controlled temperature conditions in the contact "die bearing surface – extruded profile surface" enabled the assessment of the heat transfer coefficient. The latter was found to be an order of magnitude higher (189 kW/Km²) than data known until now in the literature (8–25 kW/Km²).